AN EFFECTIVE BIOLOGICALLY ACTIVE SUBSTITUTE FOR COLON ULCER TREATMENT IS “ASKOLIT”, AGAINST FOR ULCERATIVE COLITIS - Ibragim R. Askarov; Khabibullo N. Kodirov (Academia One, 2025)
The article discusses about how effect ASKOLIT for ulcerative colitis and the distribution areas of the plants, as well as the unsurpassed role of leaves in promoting human health, the chemical composition and biological significance of vitamins ASKOLIT, as well as several recommendations for the treatment of ulcerative colitis modern medicine. traditional medicine based on the compound leaves plants Calendula officinalis and inula helenium, as well as data on the mechanism of action on the colon wall and their discussion.
Keywords: ulcerative colitis; askolit